Growth of grains in brown dwarf disks - Meru, Farzana; Galvagni, Marina; Olczak, Christoph (The astrophysical journal. Part 2, Letters, 2013)
We perform coagulation and fragmentation simulations using the new physically motivated model by Garaud et al. to determine growth locally in brown dwarf disks. We show that large grains can grow and that if brown dwarf disks are scaled-down versions of T Tauri disks (in terms of stellar mass, disk mass, and disk radius) growth at an equivalent location with respect to the disk truncation radius can occur to the same size in both disks. We show that similar growth occurs because the collisional timescales in the two disks are comparable. Our model may therefore potentially explain the recent observations of grain growth to millimeter sizes in brown dwarf disks, as seen in T Tauri disks.